2022
DOI: 10.3847/2041-8213/ac85ee
|View full text |Cite
|
Sign up to set email alerts
|

Tucana B: A Potentially Isolated and Quenched Ultra-faint Dwarf Galaxy at D ≈ 1.4 Mpc*

Abstract: We report the discovery of Tucana B, an isolated ultra-faint dwarf galaxy at a distance of D = 1.4 Mpc. Tucana B was found during a search for ultra-faint satellite companions to the known dwarfs in the outskirts of the Local Group, although its sky position and distance indicate the nearest galaxy to be ∼500 kpc distant. Deep ground-based imaging resolves Tucana B into stars, and it displays a sparse red giant branch consistent with an old, metal-poor stellar population analogous to that seen in the ultra-fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…The majority of the galaxies discovered lie in close proximity to the Milky Way (MW) and the Large Magellanic Cloud, as intrinsically faint systems are more readily detected at closer distances. A smaller number have been identified as part of the M31 satellite system, found via the targeted PAndAS observations (McConnachie et al 2009) or from DESI data (Collins et al 2022) and, more recently, a galaxy was found outside the Local Group (Sand et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the galaxies discovered lie in close proximity to the Milky Way (MW) and the Large Magellanic Cloud, as intrinsically faint systems are more readily detected at closer distances. A smaller number have been identified as part of the M31 satellite system, found via the targeted PAndAS observations (McConnachie et al 2009) or from DESI data (Collins et al 2022) and, more recently, a galaxy was found outside the Local Group (Sand et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Two overlap with the deep coverage with more stringent star-galaxy separation and are vetoed by that deeper data set. One candidate-M81-dw J0954+6821-is compact enough to show diffuse surface brightness; furthermore, the diffuse brightness is bluer in color than the resolved RGB stars, as is expected for a partially resolved dwarf galaxy (as the diffuse light is dominated by bluer subgiants and main-sequence turnoff stars; see, e.g., Figure 1 of Sand et al 2022). On this basis, we argue that it is a clear dwarf galaxy (brick red circle in Figure 2; Table 1).…”
Section: Ufd Candidate Identificationmentioning
confidence: 77%
“…Within or near the Local Group, there are two analogs to the relatively compact galaxy M81-dw J0954+6821: Pegasus V/ Andromeda XXXIV (D = 690 kpc; Collins et al 2022) and Tucana B (D = 1.4 Mpc; Sand et al 2022). In their relatively high luminosities and large sizes, M81-dw J1004+6835 and M81-dw J1000+6841 are most similar to Canes Venatici I/ Andromeda IX and Hercules/Andromeda XXIV, respectively.…”
Section: Candidate Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of the galaxies discovered lie in close proximity to the Milky Way (MW) and the Large Magellanic Cloud (LMC), as intrinsically faint systems are more readily detected at closer distances. A smaller number have been identified as part of the M31 satellite system, found via the targeted PAn-dAS observations (McConnachie et al 2009) or from DESI data (Collins et al 2022), and, more recently, a galaxy was found outside the Local Group (Sand et al 2022).…”
Section: Introductionmentioning
confidence: 99%